WHY DO THEMES MATTER? THE TEACHERS’ VOICES ABOUT THEMATIC UNITS FOR TEACHING ENGLISH TO YOUNG LEARNERS - Ivana Nabilah Qoriroh Mujahidah; Fardini Sabilah; Rina Wahyu Setyaningrum (English Review: Journal of English Education, 2022)
Teaching English to Young Learners (TEYL) in Indonesia has been an intriguing field that there never been ending studies about it. As a locally-tailored school subject that can be local content or elective subject without curriculum guideline, English for Young Learners (EYL) program is carried out in various ways by the primary schools in Indonesia. This present study aims to discover the essential role of implementing thematic model in TEYL. This paper discusses a phenomenological investigation of five EYL teachers who employ thematic units for teaching the pupils in different cities of Indonesia. Graduated from English education department, all participants have been teaching young learners English more than five years and planning their teaching based on their students’ needs by utilizing themes. Using semi-structured interview questions, the teachers were guided to explain their experience in valuing the themes for teaching English thematically, how to incorporating themes into TEYL, and challenges in implementing EYL thematic units. The data were analyzed thematically to get the emerging themes which correspond to this research topic. The results revealed that teaching English thematically is critical for young learners as their English learning scaffolding to achieve language skills and ability to communicate in particular discourse. All participants agreed that their students enjoyed the EYL thematic activities for gaining new knowledge using English despites challenges faced by the teachers in preparing the lessons.